The economic practices of US congregations: A review of current research and future opportunities. (September 2019) - Mundey, Peter; King, David P; Fulton, Brad R
Religious congregations in the US receive substantially more philanthropic contributions than any other category of organizations, yet little research has investigated how congregations receive, manage, and spend these donations. Although the economic practice of religious giving has been researched extensively, most of this research has focused on individuals or households, seeking to explain why people give to religious organizations. Relatively little research has examined the recipients of religious giving to determine how giving works within and affects these organizations. This review examines studies in the field of congregational finances, assesses available sources of data on congregations' economic practices, and concludes with recommendations for new avenues of research in this field.